Analisis Konten Digital @pocarisportid dalam Memperkuat Citra Event Pocari Sweat Run - Dafina Dewi Puspasari; Dyah Ayu Prazna Paramitha; Tria Patrianti (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
Pocari Sweat Run as an annual running event of PT. Amerta Indah Otsuka since 2013 has been the main platform to build the brand image of isotonic drinks through an inclusive offline and online hybrid experience. Instagram account @pocarisportid plays a strategic role with digital content such as race teasers, runner testimonials, and UGC content to strengthen the perception of the event as part of a healthy lifestyle. Pocari Sweat Run as one of the National running events utilizes the Instagram account @pocarisportid to convey information, value, and event experience to the audience on a regular basis. This research attempts to examine the role of digital content Instagram @pocarisportid in strengthening the image of the event Pocari Sweat Run. This research uses descriptive qualitative approach with content analysis method. Data analysis was conducted using Ardianto image theory and The Theory of Uses and Gratifications. The finding demostrated  @pocarisportid digital content was able to build a positive image of Pocari Sweat Run as a healthy, professional and inclusive running event. Promotional and educational content represents the expected image (wish image), while documentation of activities and participant testimonials reflect the mental image that emerged from the audience. In addition, digital content is able to meet the needs of information, entertainment, and social interaction of audiences. The implications of this study indicate that the management of digital content that is consistent and oriented to the needs of the audience can be an effective communication strategy in strengthening the image of sports events.